Fecal Microbiota Transplantation Improves the Quality of Life in Patients with Inflammatory Bowel Disease - Yao Wei; Weiming Zhu; Jianfeng Gong; Dong Guo; Lili Gu; Ning Li; Jieshou Li (Gastroenterology Research and Practice)
Introduction. To determine the effect of fecal microbiota transplantation (FMT) on quality of life (QoL) in patients with inflammatory bowel disease (IBD). Methods. Fourteen IBD patients, including 11 Ulcerative colitis (UC) and 3 Crohn’s disease (CD), were treated with FMT via colonoscopy or nasojejunal tube infusion. QoL was measured by IBD Questionnaire (IBDQ). Disease activity and IBDQ were evaluated at enrollment and four weeks after treatment. Patients’ attitude concerning the treatment was also investigated. Results. One patient was excluded due to intolerance. All the other patients finished the study well. Mean Mayo score in UC patients decreased significantly (5.80 ± 1.87 versus 1.50 ± 1.35, P<0.01). Mean IBDQ scores of both UC and CD patients increased (135.50 ± 27.18 versus 177.30 ± 20.88, P=0.00063, and 107.33 ± 9.45 versus 149.00 ± 20.07, P=0.024) four weeks after fecal microbiota transplantation. There was no correlation between the IBDQ score and Mayo score before and after FMT. Patients refused to take FMT as treatment repeatedly in a short time. Conlusions. Fecal microbiota transplantation improves quality of life significantly in patients with inflammatory bowel disease.